2017
DOI: 10.1039/c7sm00852j
|View full text |Cite
|
Sign up to set email alerts
|

Mode coupling theory for nonequilibrium glassy dynamics of thermal self-propelled particles

Abstract: We present a mode coupling theory study for the relaxation and glassy dynamics of a system of strongly interacting self-propelled particles, wherein the self-propulsion force is described by Ornstein-Uhlenbeck colored noise and thermal noises are included. Our starting point is an effective Smoluchowski equation governing the distribution function of particle positions, from which we derive a memory function equation for the time dependence of density fluctuations in nonequilibrium steady states. With the basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 46 publications
2
67
2
Order By: Relevance
“…It was found that the critical density at which the glass transition takes place shifts to larger values with increasing magnitude of the self-propulsion force or effective temperature, and that the critical effective glass temperature increases with the persistence time. In the limit of a vanishing persistence time, the theory naturally yields the expected result for a simple passive Brownian system [95].…”
Section: Mode-coupling Theories For Active Mattermentioning
confidence: 64%
“…It was found that the critical density at which the glass transition takes place shifts to larger values with increasing magnitude of the self-propulsion force or effective temperature, and that the critical effective glass temperature increases with the persistence time. In the limit of a vanishing persistence time, the theory naturally yields the expected result for a simple passive Brownian system [95].…”
Section: Mode-coupling Theories For Active Mattermentioning
confidence: 64%
“…The nonequilibrium nature of the system is manifested through a time-dependent effective temperature, T ef f (τ ), derived from a generalized FDR. This shows that description of such systems within a mode-coupling theoretical framework in terms of the correlation function alone [17,24,28] is incomplete. T ef f (τ ) has two distinct regimes: at very short times (τ ≪ τ p ) we have T ef f (τ ) = T and it dynamically evolves to a higher value, determined by the parameters of activity, at long time (τ ≫ τ p ).…”
Section: Discussionmentioning
confidence: 99%
“…An MCT-based scaling analysis for this type of active-matter system was later performed by Nandi and Gov [165]. Feng and Hou subsequently studied a thermal version of the active Ornstein-Uhlenbeck model that also includes thermal translational noise [109]. Their MCT derivation differs fundamentally from the approach taken by Szamel [164], however: it is valid only for sufficiently small persistence times and does not require explicit velocity correlations as input.…”
Section: B Mode-coupling Theoriesmentioning
confidence: 99%